Perlindungan Hukum Terhadap Kesalahan Diagnosis Penyakit Melalui Platform Telemedicine - Ni Putu Ayu Angreny Widhiastuty; Anak Agung Sagung Laksmi Dewi; I Gusti Agung Ayu Gita Pritayanti Dinar (Jurnal Analogi Hukum, 2024)
Health, as a human right and an essential component of well-being, needs to be realized in accordance with Indonesia's national goals. The evolution of knowledge and technology in the healthcare sector has made tremendous progress, providing the foundation for the emergence of various online health Platforms, also known as Telemedicine. The obstacles that arise along with the growth of online health Platforms in Indonesia are related to the provision of digital health services, which can open up opportunities for errors in the diagnosis process and harm Telemedicine users as patients. The formulation of the problem given is 1). How is the legal regulation of medical practice on Telemedicine Platforms in Indonesia and 2). What are the sanctions for Telemedicine Platforms due to losses suffered by patients?.